Catalytic steam reforming of glycerol over Ni–La2O3–CeO2/SBA-15 catalyst for stable hydrogen-rich gas production. (30th October 2020) - Moogi, Surendar; Lee, In-Gu; Hwang, Kyung-Ran
Abstract: Ni-based catalysts (Ni, Ni–La2 O3, and Ni–La2 O3 –CeO2 ) on mesoporous silica supports (SBA-15 and KIT-6) were prepared by an incipient wetness impregnation and tested in glycerol steam reforming (GSR) for hydrogen-rich gas production. The catalysts were characterized by the N2 -physisorption, TPD, X-ray diffraction (XRD), SEM-EDS, and TEM techniques. N2 -physisorption results of calcined catalysts highlight that adding of La2 O3 increased surface area of the catalyst by preventing pore mouth plugging in SBA-15, which was frequently observed due to the growth of NiO crystals. A set of GSR experiments over the catalysts were performed in an up-flow continuous packed-bed reactor at 650 °C and atmospheric pressure. The highest hydrogen concentration of 62 mol% was observed with a 10%Ni–5%La2 O3 –5%CeO2 /SBA-15 catalyst at a LHSV of 5.8 h −1 . Adding of CeO2 to the catalyst appeared to increase catalytic stability by facilitating the oxidative gasification of carbon formed on/near nickel active sites of Ni–La2 O3 –CeO2 /SBA-15 and Ni–La2 O3 –CeO2 /KIT-6 catalyst during the glycerol steam reforming reaction. Graphical abstract: Image 1 Highlights: Ni-based catalysts on mesoporous silica were prepared for GSR reaction. Adding of La2 O3 to Ni/SBA-15 catalyst suppressed crystalline growth of Ni. Adding of CeO2 to Ni–La2 O3 /SBA-15 catalyst facilitate carbon removal. 10% Ni–5%La2 O3 –5%CeO2 /SBA-15 catalyst showed the highest hydrogen yield.